2003
DOI: 10.1046/j.1463-1326.2003.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of treatment with acarbose or glibenclamide on insulin sensitivity in type 2 diabetic patients

Abstract: Our results show a more substantial improvement of glucose control under glibenclamide than under acarbose which, however, was not associated with an increase of insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…However, these effects do not influence total energy intake or diet nutrition composition, and no body weight loss has been observed in subjects treated with acarbose (30). Acarbose treatment improved glycemic control and insulin sensitivity without a change in postprandial insulin increment or body weight loss during a 16-week treatment study (31). Acarbose is used as an adjuvant therapy with other diabetes agents, which implies more advanced diabetic conditions and yields a higher aDCSI score than in those who do not use acarbose.…”
Section: Discussionmentioning
confidence: 96%
“…However, these effects do not influence total energy intake or diet nutrition composition, and no body weight loss has been observed in subjects treated with acarbose (30). Acarbose treatment improved glycemic control and insulin sensitivity without a change in postprandial insulin increment or body weight loss during a 16-week treatment study (31). Acarbose is used as an adjuvant therapy with other diabetes agents, which implies more advanced diabetic conditions and yields a higher aDCSI score than in those who do not use acarbose.…”
Section: Discussionmentioning
confidence: 96%
“…They are agonists for the peroxisome proliferator-activated receptor (PPAR)-γ, one of a family of nuclear receptors concerned with metabolic fuel selection and storage [13]. We incorporated a control patient group randomised to receive insulin-providing therapy with glibenclamide, which does not to affect insulin resistance or postprandial lipid metabolism [14,15]. This was administered at a low dose in order to achieve glycaemic control similar to that of the pioglitazone group, as assessed by HbA 1 c. We also studied a group of nondiabetic subjects with the aim of assessing to what extent TZD treatment restored lipid and lipoprotein metabolism to normal.…”
Section: Introductionmentioning
confidence: 99%
“…This may lie in its insulin-stimulated property. Studies indicated that insulin secretagogues reduced overall glycaemia and FBG superior to acarbose [3,13]. Other reports showed DPP-4 inhibitors were non-inferior to insulin secretagogues [14][15].…”
Section: Resultsmentioning
confidence: 99%